Use of biologics in Chinese pregnant patients with deficiency of interleukin-36 receptor antagonist (DITRA): A case series - Chang-Yu Hsieh; Yun-Ju Tsai; Tsen-Fang Tsai (Elsevier, 2024)
Objective: Impetigo herpetiformis (IH) is a rare form of pustular psoriasis which may result in maternal and fetal morbidity and even mortality. Deficiency of interleukin-36 receptor antagonist (DITRA) is the most frequently identified genetic defect of IH. Currently there are no biologics approved for IH despite the revolutionary role of biologics in the treatment of plaque and pustular psoriasis. Anecdotal reports of biologics use in DITRA patients with IH are also limited. Case reports: We present herein a case series of 6 Chinese IH patients harboring IL36RN gene c.115+6T>C mutation during 8 pregnancies, treated with various biologics, including adalimumab, etanercept and secukinumab. Conclusion: Most pregnancy courses were uneventful, except for one woman who had recurrent episodes of decreased fetal heart rate variability after adalimumab injections, which subsided after switching to etanercept. The treatment effectiveness and safety demonstrated in our cases suggested the role of biologics for the treatment of IH in patients with DITRA.